Karakterisasi Bone Graft dengan X-Ray Diffraction - Amalia, Firda; Florencia (Fakultas Kedokteran Gigi Universitas Trisakti, 2024)
Bone grafts are biomaterials that act as a scaffold for bone regeneration. It is used to fill voids and provide support. Due to its high demand, researchers have been investigating bone grafts as well as potential alternatives in order to enhance bone regeneration. A material must first be properly analysed for its characteristics as it could affect the results. One of the most commonly used characterization tools is X-Ray Diffraction, which is used to analyse the crystallinity of a material. Crystallinity is an important characteristic to analyse as it could affect degradation and bone regeneration. This article aims to provide information about bone grafts as well as the characterization of materials using X-ray Diffraction (XRD).